Factors affecting breast cancer risk level and the prevalence of early diagnosis and screening in a group of Turkish women according to the Gail model - Koca, Bennur; Acikgoz, Ayla (International Journal Of Community Medicine And Public Health, 2024)
Background: Breast cancer, which is the most prevalent and common cause of death in women in the world and Turkey, is an important public health problem. The aim of this study is to evaluate the level of breast cancer risk according to the Gail model in a group of Turkish women and to determine the factors affecting the rates of early diagnosis and screening. Methods: A cross-sectional study in Turkey. A total of 1332 women who were aged between 40 and 69 participated. The study data were collected by using a questionnaire consisting of questions about sociodemographic characteristics, lifestyle, early diagnosis and screening behaviors, and Gail model questions for determining the breast cancer risk level. Results: The risk was higher in women who had their first childbirth at the age of ≥30 years and had a first-degree relative with a history of breast cancer (p<0.05). There was a significant relationship between the breast self-examination behavior of the women and their age, education level, and family history of cancer, between their clinical breast examination behavior and age, education level, employment status, and chronic disease history, and between the behavior of getting a mammogram and age, education level, and chronic disease history (p<0.05). Conclusions: Accurate assessment of breast cancer risk and participation of women in screening programs reduce morbidity and mortality rates.